Pelatihan Pembukuan Sederhana Pada Kelompok Karang Taruna Dan Ibu-Ibu Pkk Di Desa Sukasetia, Ciamis Jawa Barat - Armiati, Reny; soraya, Elly; Asrun Putri, Aisyahpia; Fara, Sheyla; Ayunda Putri, Sylvana; Puspita Sari, Tias Ayu (Gapenas Publisher, 2022)
Good financial management is an important factor in business continuity, both small and large businesses. However, there are still many business people in rural areas who do not understand the importance of good financial records. This service aims to increase the understanding of the Suka Setia Village community about the importance of simple bookkeeping through training. The methods used are lectures and direct practice. The results of this activity show that the training participants are able to understand and practice simple bookkeeping which helps them in managing their business finances. It is hoped that this activity can be sustainable and implemented in daily business for community MSME business people in Suka Setia village.